State-Level Immigrant Prenatal Health Care Policy and Inequities in Health Insurance Among Children in Mixed-Status Families - Jessie Kemmick Pintor PhD MPH; Kathleen Thiede Call PhD (Global Pediatric Health, 2019)
Children in immigrant families are twice as likely to be uninsured as their counterparts, and states may influence these inequities by facilitating or restricting immigrant families’ access to coverage. Our objective was to measure differences in insurance by mother’s documentation status among a nationally representative sample of US-born children in immigrant families and to examine the role of state-level immigrant health care policy—namely, state-level immigrant access to prenatal coverage. Compared with US-born children in immigrant families with citizen mothers, children with undocumented immigrant mothers had a 17.0 percentage point ( P < .001) higher uninsurance rate (8.8 percentage points higher in adjusted models, P < .05). However, in states with nonrestrictive prenatal coverage for immigrants, there were no differences in children’s insurance by mother’s documentation status, while large inequities were observed within states with restrictive policies. Our findings demonstrate the potential for state-level immigrant health care policy to mitigate or exacerbate inequities in children’s insurance.